Ayurvedic Approach in the Management of Hypothyroidism: A Case Study - Sarode, Shreyash; Vidhate, Sneha; Jadhav, Jaimala; Sharma, Mahesh (Journal of Neonatal Surgery, 2025)
Hypothyroidism is a prevalent endocrine disorder characterized by insufficient thyroid hormone production, leading to various clinical manifestations such as dry skin, constipation, hair loss, and obesity. While Levothyroxine remains the conventional treatment, there is growing interest in exploring complementary therapies, particularly from traditional systems like Ayurveda. This case study presents the integrative Ayurvedic management of a 32-year-old male patient with clinically diagnosed hypothyroidism. The patient, experiencing symptoms including anorexia, fatigue, dry skin, constipation, and hair loss, was treated with a combination of Ayurvedic formulations for two months. The intervention included Chandraprabha Vati, Shigru Swaras, Nagaradi Kashaya, Kanchanara Guggulu, and Varunadi Kashaya, with the aim to rectify doshas imbalances, enhance metabolic function, and restore thyroid health. Clinical improvements were observed in symptoms, and biochemical markers (T3, T4, TSH) showed significant progress. The results suggest that Ayurvedic treatments targeting Kapha and Vata doshas, and focusing on metabolic enhancement and glandular decongestion, may provide a valuable adjunct to conventional hypothyroid management. This case highlights the potential of Ayurveda in managing hypothyroidism by addressing underlying imbalances and promoting systemic harmony.